2020
DOI: 10.1016/j.jare.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection: Emergence, transmission, and characteristics of human coronaviruses

Abstract: The coronavirus disease 19 (COVID-19) is a highly transmittable and pathogenic viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which emerged in Wuhan, China and spread around the world. Genomic analysis revealed that SARS-CoV-2 is phylogenetically related to severe acute respiratory syndrome-like (SARS-like) bat viruses, therefore bats could be the possible primary reservoir. The intermediate source of origin and transfer to humans is not known, however, the rapid human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
2,878
2
253

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,514 publications
(3,384 citation statements)
references
References 73 publications
12
2,878
2
253
Order By: Relevance
“…This is followed by assembly and budding into the lumen of the ERGIC. Virions are then released from the infected cell through exocytosis [91]. NSP, nonstructural proteins; ACE2, Angiotensin-Converting Enzyme 2; Rough ER, Rough Endoplasmic Reticulum; ERGIC, Endoplasmic Reticulum Golgi Intermediate Compartment.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This is followed by assembly and budding into the lumen of the ERGIC. Virions are then released from the infected cell through exocytosis [91]. NSP, nonstructural proteins; ACE2, Angiotensin-Converting Enzyme 2; Rough ER, Rough Endoplasmic Reticulum; ERGIC, Endoplasmic Reticulum Golgi Intermediate Compartment.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This highly transmittable and pathogenic viral belongs to the subfamily Orthocoronavirinae in the family of Coronaviridae, in the order Nidovirales (4). The subfamily of coronaviruses family includes alpha (α), beta (β), gamma (γ) and delta (δ) coronavirus (5).…”
Section: Sars-cov-2: Prevalence Phylogenetics Taxonomy and Structurmentioning
confidence: 99%
“…SARS-CoV2 is a novel β-coronavirus after the previously identified SARS-CoV and MERS-CoV which led to pulmonary failure and potentially fatal respiratory tract infection and caused outbreaks mainly in Guandong, China and Saudi Arabia. In COVID- 19 research, many studies have demonstrated that bats are suspected as the key reservoir of the viruses by finding as much as 96.2% identical genome sequencing of SARS-CoV-2 with bat CoV RaTG13 [3,7]. In this review, we hypothesize that since the COVID-19 virus has several complex immune-evasion components that contribute to its virulence, we suggest this more complete understanding can be used to develop an effective approach in the treatment of diseases caused by this virus.…”
Section: Introductionmentioning
confidence: 99%